Recent advances in the management of acute promyelocytic leukemia - Abdelhamid Mohamed Fouad; Mohamed Abdelmooti Mohamed; Raafat Mohamed Abdelfattah; Thoria Mohamed Abdelhamid (Cairo : Abdelhamid Mohamed Fouad, 2010)
Acute promyelocytic leukemia (APL) was first identified as a distinct subtype of acute myeloid leukemia in 1957 by leif hillestad . It is called M3 in the French - American - British classification with a variant type referred to as microgranular (M3v in the French - American - British nomenclature ) APL acounts for 10% - 15% of all cases of acute myeloid leukemia with several thousand new cases diagnosed worldwide each year
Thesis (M.Sc.) - Cairo University - National Cancer Institute - Department of Oncology-Medicine
Issued also as CD
Keywords: Acute myeloid leukemia; Acute promyelocytic leukemia; Arsenic trioxide